Motives for Choosing a Profession and Teachers' Job Satisfaction - Katarzyna Nowosad (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction: Job satisfaction is a function of meeting the employee's needs and depends on his individual professional expectations and motives for choosing a profession and the extent to which they have been fulfilled in a specific work situation. Thus, individual needs motivating the choice of the teaching profession are an important factor determining the extent to which the current work is beneficial for them. Thus, it is a typical psychological reaction to a professional situation, expressed through affective reactions and cognitive assessments. Job satisfaction plays an important role in the professional development of teachers, their effective performance and gives them a sense of quality of life. Research Aim: The aim of the research was to determine the relationship between the motives for choosing a profession and teachers' job satisfaction. Method: The study used the method of diagnostic survey, survey technique and questionnaire. Elements of descriptive and correlation statistics (rho-Spearman linear correlation coefficient) were used for the analysis of the research material. Results: The issue of the dependence of job satisfaction on the motives for choosing a profession is the subject of these empirical analyses. The obtained research results confirm the fully adopted assumption of a significant relationship between these variables. Conclusions: When choosing the profession of a teacher, people are guided mainly by internal motivation, i.e. personal interests, willingness to work with children and youth, a specific pedagogical vocation. For a significant number of teachers, an important motive is also the teacher's convenient working time and job security guaranteed by law. The structure of internal motives shaped in this way fundamentally determines teachers' satisfaction with their profession.